Strategiia pobedy . Strategiia pobedy . Strategy of Victory . Стратегия победы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. History of atrocities in the Second World War and the fall of the Fascist regime. The program is based on archival records and highlights the following historical figures: J.V. Stalin, Franklin Roosevelt, Winston Churchill, Adolf Hitler, and Benito Mussolini. Featured in the program: Goloborod'ko, Aleksandr (Historian) Contributors: Belianinov, Stanislav (Director); Lanovoi, Vasilii (Anchor); Vats, Kirill (Anchor); Nikiforov, Gennadii (Anchor); Braun, Heinz (Anchor); Zasukhin, Nikolai (Anchor); Tel'pukhovskaia, E. (Editor); Meletin, Vladimir (Camera); Tvorcheskoe ob"edinenie "Ekran" (Studio) История Второй мировой войны: военные действия и падение фашистского режима. Программа основана на архивных записях. Её участники: Сталин И. В., Франклин Делано Рузвельт, Уинстон Черчилль, Адольф Гитлер, Бенито Муссолини. В программе участвуют: Голобородько, Александр (Историк) Создатели: Белянинов, Станислав (Режиссер); Лановой, Василий (Ведущий/Ведущая); Вац, Кирилл (Ведущий/Ведущая); Никифоров, Геннадий (Ведущий/Ведущая); Браун, Хайнц (Ведущий/Ведущая); Засухин, Николай (Ведущий/Ведущая); Тельпуховская, Э. (Редактор); Мелетин, Владимир (Оператор); Творческое объединение "Экран" (Студия)